2005
DOI: 10.1192/bjp.186.6.476
|View full text |Cite
|
Sign up to set email alerts
|

Acute military psychiatric casualties from the war in Iraq

Abstract: These findings have implications especially for screening for suitability for deployment, and for understanding any longer-term mental health problems arising in veterans from Iraq.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 9 publications
0
25
0
1
Order By: Relevance
“…The authors showed that most evacuations were for adjustment disorders (37%), mood disorders (22%), personality disorders (16%) and anxiety disorders (includes PTSD, 15%) [11]. A U.K. study found just over half of evacuations were for adjustment disorders [23]. Our study found that homicidal/suicidal ideation (not a discrete category in the previous studies), mood disorders, PTSD and psychosis had the highest rates of MEDEVAC.…”
Section: Discussionmentioning
confidence: 50%
“…The authors showed that most evacuations were for adjustment disorders (37%), mood disorders (22%), personality disorders (16%) and anxiety disorders (includes PTSD, 15%) [11]. A U.K. study found just over half of evacuations were for adjustment disorders [23]. Our study found that homicidal/suicidal ideation (not a discrete category in the previous studies), mood disorders, PTSD and psychosis had the highest rates of MEDEVAC.…”
Section: Discussionmentioning
confidence: 50%
“…More recent research based on military personnel deployed to Iraq or Afghanistan has produced mixed results. Although the majority of these studies have revealed few differences in health status following deployment (Hoge, Aucherlonie, & Milliken, 2006;Kang & Hyams, 2005;Seal et al, 2007), studies of U.K. veterans have generally demonstrated poorer health outcomes for reservists relative to "regular" military personnel (Hotopf et al, 2006;McAllister, Blair, & Philpott, 2004;Turner, Kiernan, McKechanie, Finch, McManus, & Neal, 2005). What these studies have in common is that they do not address differences in reports of deployment stressors or differential associations with health outcomes, as was done in the present study.…”
mentioning
confidence: 52%
“…Many studies have been carried out into the psychological effects of war on military personnel (e.g., Hacker Hughes et al, 2005;Hoge et al, 2004;Ikin et al, 2004;Turner et al, 2005). The existing literature suggests that mental health problems have been identified in veterans of recent conflicts.…”
Section: Military Mental Healthmentioning
confidence: 97%